A novel false-positive cause in testis scintigraphy in the diagnosis of testis torsion - Koç, Zehra Pinar; Onur, Rahmi; Balci, Tansel Ansal (BMJ Publishing Group, 2012)
Testis scintigraphy is the most reliable modality in the diagnosis of testis torsion since it directly reflects the vascularity of the testis. The 'rim sign' is considered as the pathognomonic sign of the missed torsion. However, there are some possible false-positive cases. In this case report, we would like to present an unexpected false-positive cause of the 'rim sign' in testis scintigraphy in an 18-year-old male patient. Copyright 2012 BMJ Publishing Group. All rights reserved.
Keywords: pertechnetic acid tc 99m; adult; article; case report; color ultrasound flowmetry; false positive result; fibrosis; human; image analysis; image display; male; male genital system surgery; priority journal; scar; scrotal pain; testicular enlargement; testis scintigraphy; testis torsion; tissue adhesion; urogenital scintiscanning; varicocelectomy